Quality analysis of pre-release rice cultures of KAU - Sugeetha T S (Department of Home Science, College of Agriculture, 2010)
“Quality analysis of pre-release rice cultures of KAU” was a study undertaken to determine the quality aspects of the pre-release rice varieties by assessing parameters like physical characteristics, cooking characteristics, nutritional composition and organoleptic qualities. The effect of parboiling on the above quality aspects was also studied.